Variations in hemoglobin measurement and eligibility criteria across blood donation services are associated with differing low‐hemoglobin deferral rates: a BEST Collaborative study. Issue 3 (8th February 2020) - Zalpuri, Saurabh; Romeijn, Bas; Allara, Elias; Goldman, Mindy; Kamel, Hany; Gorlin, Jed; Vassallo, Ralph; Grégoire, Yves; Goto, Naoko; Flanagan, Peter; Speedy, Joanna; Buser, Andreas; et al.
Abstract : BACKGROUND: Determination of blood donor hemoglobin (Hb) levels is a pre‐requisite to ensure donor safety and blood product quality. We aimed to identify Hb measurement practices across blood donation services and to what extent differences associate with low‐Hb deferral rates. METHODS: An online survey was performed among Biomedical Excellence for Safer Transfusion (BEST) Collaborative members, extended with published data. Multivariable negative‐binomial regression models were built to estimate adjusted associations of minimum donation intervals, Hb cut‐offs (high, ≥13.5 g/dL in men or ≥ 12.5 g/dL in women, vs. lower values), iron monitoring (yes/no), providing or prescribing iron supplementation (yes/no), post‐versus pre‐donation Hb measurement and geographical location (Asian vs. rest), with low‐Hb deferral rates. RESULTS: Data were included from 38 blood services. Low‐Hb deferral rates varied from 0.11% to 8.81% among men and 0.84% to 31.85% among women. Services with longer minimum donation intervals had significantly lower deferral rates among both women (rate ratio, RR 0.53, 95%CI 0.33‐0.84) and men (RR 0.53, 95%CI 0.31‐0.90). In women, iron supplementation was associated with lower Hb deferral rates (RR 0.47, 95%CI 0.23‐0.94). Finally, being located in Asia was associated with higher low‐Hb deferral rates; RR 9.10 (95%CI 3.89‐21.27) for women and 6.76 (95%CI 2.45‐18.68) for men. CONCLUSION: Differences in Hb measurement and eligibility criteria, particularly longer donation intervals and iron supplementation in women, are associated with variations in low‐Hb deferral rates. These insights could help improve both blood donation service efficiency and donor care.